Dietary intake and major sources of plant lignans in Latvian men and women. (August 2013) - Meija, Laila; Söderholm, Paivi; Samaletdin, Adile; Ignace, Gita; Siksna, Inese; Joffe, Rafaels; Lejnieks, Aivars; Lietuvietis, Vilnis; Krams, Indrikis; Adlercreutz, Herman
<x xml:space="preserve">Abstract</x> Higher intake of lignans, diphenolic plant compounds, may reduce the risk of certain types of cancer and cardiovascular diseases. We assessed the dietary intake of four lignans: matairesinol, secoisolariciresinol, lariciresinol and pinoresinol. Furthermore, for the breads we supplemented the data with two more lignans: syringaresinol and medioresinol. Study subjects were 172 men and 97 women aged 40–75 years, residing in Riga, the capital of Latvia, all living at home, eating habitual food. Median total lignan intake was 2259 (range 1169–5759) μg/day. Secoisolariciresinol contributed 58% and syringaresinol 22% of lignan intake. Bread was the major food source of lignans in men (86%), whereas in women it was bread (57%) and flaxseed (35%).